Barium carbonate and barium titanate for ultra-high temperature thermochemical energy storage - Williamson, Kyran; D'Angelo, A.M.; Humphries, Terry; Paskevicius, Mark; Buckley, C.E. (2024)
The significance of energy storage should not be underestimated in enabling the growth of renewables on the path towards decarbonisation. In this research, a novel ultra-high temperature reactive carbonate composite, 2BaCO3:TiO2, is introduced. Upon heating, the composite initially forms a mixture of BaCO3:BaTiO3, which on further heating reacts to form Ba2TiO4 and CO2 in a reversible thermochemical reaction. The enthalpy and entropy of the carbonation reaction involving Ba2TiO4 were determined manometrically to be ∆H = 295 ± 9 kJ∙mol−1 of CO2 and ∆S = 214 ± 7 J∙K−1∙mol−1 of CO2, respectively. The CO2 cycling capacity of the composite was evaluated using a Sieverts apparatus and thermogravimetric analysis, and sintering was identified as a potential cause of capacity loss. The addition of nickel was employed to mitigate the effect of sintering, resulting in a stable reversible capacity of up to 50 % of the theoretical maximum. The composite's cyclic capacity retention, low cost, and high energy storage density make it a promising candidate for energy storage applications at ≈ 1100 °C, although improvement to the cyclic capacity would lead to a more favourable application potential.